THE IMPLICATIONS OF OCCUPATIONAL SAFETY AND HEALTH, DISCIPLINE, AND MOTIVATION ON EMPLOYEE PERFORMANCE AND PRODUCTIVITY AT PT. SARANA WARNA MEGAH SURABAYA - Iman, Nurul; Nitawati, Elly Yuniar; Triandani, Dita (UTSAHA: Journal of Entrepreneurship, 2023)
The industrial sector is experiencing competitive pressure as a function of the desire to better manage its resources, especially their human resources. Therefore, the corporation must create the most of its efforts to improve these human resources if it is to attain high levels of employee performance and productivity. The targets or goals for PT. Sarana Warna Megah are not even reached because of several their employee problems. The objective of this research is to indicate and examine the potential simultaneous, partial, and dominating impacts that work discipline, motivation, and occupational safety and health variables may have on employee performance and productivity at PT. Sarana Warna Megah Surabaya. 60 respondents composed the sample for this research. Probability sampling was used to conduct out the sampling process. Multiple linear regression analysis is the analysis method employed, and the f-test (simultaneous), t-test (partial), and dominant are utilized for hypothesis testing. The results of this research indicate that employee performance and productivity are significantly influenced by work discipline, motivation, and occupational safety and health. The findings indicate that factors such as work discipline, motivation, and occupational safety and health have a partial impact on employee performance and productivity. Occupational discipline and motivation are other factors that affect employee performance and productivity, but occupational safety and health are the ones that have the biggest impact.